Psychological impact of adverse childhood experiences and ostracism on depression among Malaysian youth - Rehman, Shabina; Rehman, Asad Ur; Yousuff, Nazirah Yasmin Binti Mohamed; Zayed, Muhammad Az-Zuhri bin; Dullet, Gurbir (University of Muhammadiyah Malang, 2024)
This study aimed to examine the relationship between adverse childhood experiences, ostracism and depression among young adults in Shah Alam, Malaysia. This research was made to contribute a clearer understanding of the prevalence of depression amongst young adults. The study used a quantitative, cross-sectional research design with non-probability sampling and the data was analyzed using structural equation modelling (SEM). Two hundred fifty respondents aged 18 - 29 from Shah Alam, Malaysia, participated. The Depression, Anxiety and Stress Scale - 21 Items (DASS-21), Adverse Childhood Experiences Questionnaire and Ostracism Experiences Scale (OES) were used in this study. Results have shown that there is a significant relationship between adverse childhood experiences, ostracism, and depression among young adults. Direct effects were assessed in a structural model. Adverse childhood experiences and ostracism both have significant effects on depression. Adverse childhood experiences positively affect depression (β = 0.423, p < 0.001), while ostracism also has an adverse effect on depression (β = 0.534, p < 0.001). In conclusion, these findings contribute to the knowledge that early life traumatic events and ignorance can influence a young adult psychologically.